Method for improving grease and oil resistance of textile products

A composition of acrylamide copolymer and cationic polymer components with specific charge densities enhances oil and grease resistance in molded fiber products, addressing the limitations of current technologies and enabling cost-effective, biodegradable solutions for food packaging.

JP2025501087APending Publication Date: 2025-01-17KEMIRA OY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024536989
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-01
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Current fiber technology is not suitable for use as lids for containers of meat and poultry, prepared foods, manufactured foods, and beverages due to the lack of effective oil and grease resistance, and incorporating barriers is tedious, time-consuming, and costly.

Method used

A method involving a composition comprising a synthetic polymer component, such as a copolymer of acrylamide and an anionic monomer, and a cationic polymer component, with specific charge densities, is introduced into cellulose fibers to enhance oil and grease resistance, which can be shaped into textile products.

Benefits of technology

The method provides improved oil and grease resistance in molded fiber products, allowing for reduced thickness and weight, while maintaining biodegradability and compostability, and can be produced in a simple and low-cost manner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501087000001_ABST
    Figure 2025501087000001_ABST
Patent Text Reader

Abstract

A method for improving the grease and oil resistance of a molded textile product is provided. The method includes introducing a composition including a synthetic polymer component and a cationic polymer component into a textile raw material and thermoforming the textile raw material. Molded textile products and the use of the composition for improving the grease and oil resistance of molded textile products are also provided. A method for producing a molded textile product is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to a method for improving the grease and oil resistance of textile products, and more particularly, but not by way of limitation, to a method for improving the grease and oil resistance of textile products by shaping textile raw materials.

[0002] Please note that this section provides useful background information, but is not an admission that the technology described herein represents the state of the art.

[0003] Pollution from single-use plastic packaging and materials is widespread, marring the world's landscapes and threatening delicate ecosystems and the life forms that inhabit them. Single-use packaging travels through waterways and into oceans in the form of Styrofoam and Expanded Polystyrene (EPS) packaging, take-out containers, bottles, thin film bags, photodegradable plastic pellets, and more. Sustainable solutions to reduce plastic pollution are gaining momentum. However, sustained adoption requires that these solutions are not only environmentally good, but also competitive with plastics in terms of both performance and cost.

[0004] To provide some brief background, molded paper pulp products (fiber molded products) have been used for packaging such as containers and trays since the 1930s, but declined in the 1970s with the advent of fossil fuel-based foamed plastic packaging. Paper pulp can be produced from old newspapers, cardboard boxes, and other plant fibers. Today, molded pulp packaging is widely used for electronics, household goods, auto parts, and medical products, and is also used as edge / corner protectors and pallet trays when transporting electronic and other fragile parts.

[0005] Packaging products based on cellulose fibers are biodegradable and compostable and, unlike fossil fuel-derived plastics, do not migrate into the ocean. However, currently known fiber technologies are not suitable for use as closures for meat and poultry, cooked and prepared foods, microwaveable foods, and beverage containers such as hot coffee. In particular, selectively incorporating oil, water, steam, and / or oxygen barriers into slurries and / or selectively applying one or more barrier layers to all or a portion of the surface of a finished packaging product can be tedious, time-consuming, and costly.

[0006] Depending on the application of the molded pulp and the type of container, barrier properties against oil, grease, water, water vapor, oxygen and / or other gases and liquids are required. The use of appropriate slurry chemistry can result in improved process efficiency, mechanical properties, barrier properties and / or surface coatability, making the production of molded pulp products more competitive with those made from flat board. Abstract

[0007] According to a first aspect, the present invention provides a method for improving the grease and oil resistance of a molded textile product, the method comprising: Obtaining a fiber raw material comprising cellulosic fibers; introducing a composition into said fiber material; wherein the composition comprises a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and −0.2 to −3 meq / g when measured at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw material; forming the fiber material; Includes.

[0008] According to a second aspect, the invention provides a molded fiber product comprising a composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and −0.2 to −3 meq / g when measured at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; wherein said shaped textile product is produced by a method according to the invention.

[0009] According to a third aspect, the present invention provides the use of a composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and -0.2 to -3 meq / g when measured at pH 7.0, In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; Some embodiments include pigments to improve the grease and oil resistance of the molded fiber.

[0010] Surprisingly, it has now been found that molded textiles (e.g., thermoformed textiles) containing a composition comprising a synthetic polymer component and a cationic polymer component, such as a cationic starch component, having a particular charge density, have excellent oil resistance. Surprisingly, it has been found that the composition acts as an oil barrier in the textile. It is also believed that the composition acts as a grease barrier in the textile.

[0011] The composition has been found to provide superior resistance to olive oil, i.e., resistance to penetration time and uptake, as compared to molded textile products not containing the composition, and also appears to provide grease resistance.

[0012] Additionally, it has been surprisingly found that molded fiber products comprising this composition and polyamidoamine epichlorohydrin (PAAE), glyoxalated polyacrylamide, starch, or mixtures thereof, have improved oil resistance and are believed to have improved grease resistance.

[0013] It has been found that the incorporation of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof in the above composition improves the oil resistance of molded textiles (e.g., thermoformed textiles) by as much as 60 minutes compared to molded textiles without the use of the above composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, or mixtures thereof, and is believed to improve grease resistance as well.

[0014] It is believed that, without being bound by any theory in this regard, the molded textile containing the composition including the synthetic polymer component and the cationic polymer component traps grease and oil components and acts as a grease and oil barrier.

[0015] The textile products of the present invention are at least partially biodegradable and compostable, preferably mostly biodegradable and compostable, more preferably substantially completely biodegradable and compostable, and most preferably biodegradable and compostable.

[0016] It has also been surprisingly found that textile products with oil and grease resistance can be produced in a simple and cost-effective manner. It has been found that textile products with grease and / or oil resistance can be produced by introducing a textile raw material containing a composition with a specific charge density, the composition comprising a synthetic polymer component and a cationic polymer component, into a textile raw material containing cellulosic fibers, and molding (e.g., thermoforming) the textile raw material. In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or a mixture thereof is introduced prior to molding.

[0017] Surprisingly, it has been found that by incorporating the composition in large amounts (e.g. 5-50 kg / t based on the dry weight of the fiber raw material) into the fiber raw material, the molded articles produced have high oil resistance. The oil resistance is further increased by additionally incorporating polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof into the fiber raw material. It is also believed that the grease resistance is improved.

[0018] It has further been found, surprisingly, that the molded textiles described above (e.g., thermoformed textiles) have improved bending stiffness because, surprisingly, they have been found to have improved tensile bending stiffness compared to molded textiles that do not include the composition or the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof. The improved tensile index and tensile bending stiffness may allow the thickness of the molded textile to be reduced, and therefore the mass per unit area of ​​the molded textile.

[0019] The thickness and mass per unit area can be reduced, which will reduce the weight of textile products, and therefore the cost of textile raw materials.

[0020] It is also believed that the addition of the composition, or the composition together with polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw materials in the board manufacturing process will impart grease and oil resistance to the board.

[0021] It has also been found that the addition of pigments and / or other additives to the composition prior to igniting the composition on the textile raw materials improves the gloss, smoothness, coatability and / or barrier properties of the molded textile product. The appended claims define the scope of protection. [Brief description of the drawings]

[0022] [Figure 1] The olive oil resistance of a two-dimensional molded fiber product (400 g / m2) after heat press drying and thermoforming (in the thickness direction) at 40° C. is shown for the composition used in the method of the present invention (composition B) and for the comparative composition A. [Diagram 2]This refers to a thermoformed two-dimensional textile product or textile sheet. [Diagram 3] 1 shows a wet molded and thermoformed three-dimensional textile product. Detailed explanation

[0023] According to a first aspect, the present invention provides a method for improving the grease and oil resistance of a molded textile product, the method comprising: Obtaining a fiber raw material comprising cellulosic fibers; introducing a composition into said fiber material; wherein the composition comprises a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and −0.2 to −3 meq / g when measured at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, to the fiber raw material; forming the fiber material; Includes.

[0024] The synthetic polymer component and the cationic polymer component of the composition provide charge density to the composition.

[0025] In some embodiments, polyamidoamine epichlorohydrin (PAAE), glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material. Preferably, polyamidoamine epichlorohydrin is introduced into the fiber raw material.

[0026] In some embodiments, a pigment is introduced into the fiber raw material.In some embodiments, the pigment is introduced into the fiber raw material before adding the composition to the fiber raw material.

[0027] In some embodiments, the pigment is introduced to the fiber raw material after the composition is added to the fiber raw material. In some embodiments, the pigment is introduced to the fiber raw material at the same time as the composition is added to the fiber raw material.

[0028] In some embodiments, the pigment and the composition are introduced to the fiber material as a mixture.

[0029] In some embodiments, the pigment comprises talc, kaolin clay, calcium carbonate, or mixtures thereof.

[0030] The molding, i.e., molding step or process, can be any suitable method known in the art.

[0031] In some embodiments, forming includes wet forming, wet forming, vacuum forming, vacuum forming, extrusion, extrusion, thermoforming, dry forming, heat pressing, heat press drying, thermoforming, heat pressing, thermoforming, or combinations thereof, preferably thermoforming, more preferably heat pressing, heat press drying or thermoforming.

[0032] In some embodiments, the fiber material is formed into a sheet.

[0033] In some embodiments, the fibrous material is formed into a sheet, preferably by thermoforming into a sheet.

[0034] As used herein, the term "sheet" means an article having a thickness that is less than its length and width.

[0035] In this application, the term "two-dimensional product" refers to a two-dimensional product that is originally made into a flat shape and has a thickness that is less than its length and width. The two-dimensional product can be folded or bent into a three-dimensional product.

[0036] As used herein, the terms "three-dimensional product" and "3D product" refer to a product that has three dimensions.

[0037] For purposes of this application, a sheet is not considered a three dimensional product.

[0038] In some embodiments, the sheet is formed into a three-dimensional article.

[0039] In some embodiments, the fibrous material is formed into a three-dimensional article.

[0040] In some embodiments, the fibrous raw material with or without foam is vacuum formed or extruded, wet pressed and / or drained with the aid of vacuum, dried unconstrained and / or constrained, compressed in one or more directions, polymer impregnated, polymer laminated, polymer coated or a combination thereof into a two-dimensional sheet having a thickness of 0.1 mm to 10 mm, preferably 0.3 mm to 2 mm. In some embodiments, the 2D sheet is further thermoformed (i.e. dry formed) into a three-dimensional product, preferably having a length and width of 5 cm to 50 cm, a depth of 2 cm to 20 cm and a wall thickness of 0.1 mm to 2 mm.

[0041] In some embodiments, the fibrous material is wet shaped and the wet shaped fibrous material is formed into a three-dimensional article.

[0042] Depending on the embodiment, the temperature of the mold in the heat press, hot press, hot press drying, thermoforming or thermoforming is 100°C to 400°C, preferably 130°C to 200°C.

[0043] In some embodiments, the mechanical pressure applied to the fiber raw material or the two-dimensional or three-dimensional fiber product during heat pressing, hot pressing, hot press drying or thermoforming is between 0.1 bar and 1000 bar, preferably up to 20 bar, and depending on the production technique, the equipment and the application of the fiber molded product, the pressure may vary during heat pressing, hot pressing, hot press drying or thermoforming.

[0044] In some embodiments, the shaping is shaping into a three-dimensional article, including thermoforming, heat pressing, thermoforming, wet or dry forming to densify, and / or wet or dry forming, or combinations thereof.

[0045] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof and the composition are introduced sequentially to the fiber raw material. Preferably, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced to the fiber raw material prior to introducing the composition to the fiber raw material.

[0046] In some embodiments, the composition is introduced into a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof into the fiber raw material.

[0047] In some embodiments, the synthetic polymer component and the cationic polymer component are introduced sequentially to the fiber raw material. Preferably, the cationic polymer component is introduced to the fiber raw material before the synthetic polymer component is introduced to the fiber raw material.

[0048] In some embodiments, the synthetic polymer component is introduced into a fiber raw material followed by the cationic polymer component.

[0049] In some embodiments, the synthetic polymer component, the cationic polymer component, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced sequentially to a fiber raw material.

[0050] In some embodiments, the synthetic polymer component and the cationic polymer component are introduced sequentially to a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw material.

[0051] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to a fiber raw material, followed by sequentially introducing the synthetic polymer component and the cationic polymer component to the fiber raw material.

[0052] In some embodiments, the synthetic polymer component is introduced to a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, to the fiber raw material, and then introduction of the cationic polymer component to the fiber raw material.

[0053] In some embodiments, the cationic polymer component is introduced to a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, to the fiber raw material, and then introduction of the synthetic polymer component to the fiber raw material.

[0054] In some embodiments, the compositions contain both anionic groups, primarily derived from a synthetic polymer component, and cationic groups, primarily derived from a cationic polymer component (e.g., a cationic starch component). The net charge of the compositions is carefully selected to provide optimal behavior during preparation, storage and / or transportation of the compositions, as well as at the various pH values ​​encountered during use.

[0055] In some embodiments, the synthetic polymer component and cationic polymer component (e.g., cationic starch component) of the present invention provide a composition having a charge density of 0.1 to 0.5 meq / g, preferably 0.15 to 0.3 meq / g, when measured at pH 2.8. Also provided are compositions having a charge density of -0.4 to 2.0 meq / g, preferably -0.5 to -1.5, when measured at pH 7.0. According to some embodiments of the present invention, the composition may have a charge density of -0.3 to 3.0 meq / g, preferably -0.4 to 3.0 meq / g, more preferably -0.5 to 3.0 meq / g, when measured at pH 7.0. A defined charge density at pH<3.5 is suitable to provide easy handling of the composition, and a charge density at pH>3.5 is sufficient to ensure the presence of anionic charges to provide effective interaction with both the cationic polymer component and the fiber and fillers in the raw material.

[0056] In a preferred embodiment, the composition already has an anionic net charge at pH 5.5, preferably already has an anionic net charge at pH 5.0, more preferably already has an anionic net charge at pH 4.5.

[0057] When the pH value of the composition is <3.5, the charge density of the composition is primarily due to the cationic groups of the cationic polymer component, such as the cationic starch component. At pH values ​​>3.5, the charge density of the composition is primarily due to the anionic groups of the synthetic polymer component. The synthetic polymer component may have a charge density of -0.3 to -7 meq / g at pH 7, preferably -0.5 to -5 meq / g, more preferably -1 to -3 meq / g, and even more preferably -1 to -2 meq / g, i.e., is anionic at pH 7.

[0058] In some embodiments, the composition may have a pH value below 3.5. The composition may also have a dry solids content during manufacture, transportation and / or storage in the range of 5-30% by weight, preferably 10-20% by weight, more preferably 12-17% by weight. At acidic pH values ​​< 3.5, the anionic groups of the polymeric component are in the acid form. As the pH value decreases, the interaction between the anionic groups of the synthetic polymeric component and the cationic polymeric component decreases. For example, at pH values ​​below 3.2, the anionic groups of the synthetic polymeric component undergo little or no interaction with the charged cationic polymeric component. This results in a low viscosity that is easy to prepare and handle the composition, even at high solids. A high solids content of the composition is economical from the standpoint of storage and transportation, since less space is required for the same amount of active ingredient. The pH of the composition may be adjusted to a value < 3.5 by the addition of an acid.

[0059] In some embodiments, when the composition is ready to be added to the fiber raw material, it may be diluted with water and have a final pH value of 3.8 to 6.0, preferably 4 to 5.5. It may also have a dry solids content of less than 10% by weight, preferably less than 5% by weight, more preferably less than 0.5 to 4.5% by weight after dilution. Typically, the composition may exhibit both cationic and anionic charges at the final pH, i.e., at the time of addition. A defined charge density at pH>3.5 is sufficient to provide effective interaction with both the cationic polymer component as well as the fiber and / or filler in the raw material. Furthermore, it has been observed that the composition may be effectively mixed with the raw material at the wet end of a paper or board machine when the solids content is less than 10% by weight. A solids content of less than 5% is particularly preferred when the starch component comprises non-degraded starch.

[0060] In some embodiments, the composition comprises 10-90% by weight, preferably 30-70% by weight, more preferably 40-60% by weight, of a synthetic polymer component and 10-90% by weight, preferably 30-70% by weight, more preferably 40-60% by weight, of a cationic polymer component (such as a cationic starch component), calculated on the dry weight of the composition. In a preferred embodiment, the ratio of synthetic polymer component to cationic polymer component (such as a cationic starch component) is 40:60 to 60:40 by dry weight. The ratio of synthetic polymer to cationic polymer component is selected such that the composition is net anionic at the pH of the fiber raw material.

[0061] The synthetic polymer component of the composition may be a copolymer of acrylamide and at least one anionic monomer. The copolymer may be linear or crosslinked. The synthetic polymer may be prepared by any suitable polymerization method, such as solution polymerization, dispersion polymerization, emulsion polymerization, gel polymerization, or bead polymerization. In some embodiments, the synthetic polymer component of the composition is prepared by polymerization of acrylamide and at least one anionic monomer. The anionic monomer is selected from unsaturated mono- or dicarboxylic acids or salts thereof, such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, crotonic acid, isocrotonic acid, or mixtures thereof. The synthetic polymer component is preferably prepared by solution polymerization of acrylamide and acrylic acid.

[0062] When the synthetic polymer components are crosslinked, a crosslinking agent is used in the polymerization, the amount of the monomer being 100-1000 mg / kg, preferably 100-500 mg / kg. Suitable crosslinking agents include, for example, methylenebisacrylamide, ethylene glycol divinyl ether, di(ethylene glycol) divinyl ether, tri(ethylene glycol) divinyl ether. However, methylenebisacrylamide is preferred.

[0063] In some embodiments, the synthetic polymer components are not crosslinked at all or are only slightly crosslinked, in such embodiments, a crosslinker is used in the polymerization in an amount of 0.25-100 mg / kg of monomer, preferably 0.5-10 mg / kg, more preferably 0.75-5 mg / kg.

[0064] The synthetic polymer component may have an anionicity of 3-40 mol%, preferably 5-18 mol%, more preferably 9-15 mol%. The anionicity relates to the amount of structural units derived from anionic monomers in the synthetic polymer component. The anionicity of the synthetic polymer component is selected to optimize the binding of the composition with fibers, fillers and other components in the raw material. If the amount of units derived from anionic monomers is too low, the composition will not exhibit the desired anionic net charge and will not achieve the desired binding effect. On the other hand, if the amount of units derived from anionic monomers is too high, too little dosage will be required to induce the desired effect.

[0065] In some embodiments, the synthetic polymer component of the present invention, preferably prepared by solution polymerization, may have a weight average molecular weight MW of 300000 g / mol or more, preferably 500000 g / mol or more. Preferably, the weight average molecular weight of the synthetic polymer component may be 300000-1000000 g / mol, more preferably 400000-1000000 g / mol, even more preferably 500000-900000 g / mol. The average molecular weight of the synthetic polymer component is carefully selected to provide optimal performance in the composition. It has been observed that if the average molecular weight is too high, the viscosity of the composition becomes too high at a useful solids content, and the solids content becomes too low to achieve the appropriate viscosity.

[0066] In some embodiments, the synthetic polymer component is obtained by first adiabatic gel polymerization, followed by drying and then bead polymerisation in a solvent or emulsion or dispersion polymerization in an aqueous salt medium, and has an average molecular weight MW in the range of 2 000 000-18 000 000 g / mol, preferably 4 000 000-10 000 000 g / mol.

[0067] In this application, the value of "average molecular weight" is used to indicate the size of the polymer chain length and indicates the weight average molecular weight of the polymer. The value of the average molecular weight is calculated from the results of the intrinsic viscosity measured by a known method using an Ubbelohde capillary viscometer in 1N NaCl at 25°C. The capillary is selected appropriately, and in the measurements of this application, an Ubbelohde capillary viscometer with a constant K = 0.005228 was used. The average molecular weight is then calculated from the results of the intrinsic viscosity by a known method using the Mark-Houwink equation [η] = K-Ma, where [η] is the intrinsic viscosity, M is the molecular weight (g / mol), and K and a are parameters described for polyacrylamide in the following literature: Polymer Handbook, Fourth Edition, Volume 2, Editors: J. Brandrup, EH Immergut and EA Grulke, John Wiley & Sons, Inc., USA, 1999, p.VII / 11.

[0068] Thus, the value of the parameter K is 0.0191 ml / g and the value of the parameter a is 0.71. The range of average molecular weight given in the parameters of the conditions of use is 490000-3200000 g / mol, but the same parameters are used to describe the magnitude of the molecular weight outside this range. For polymers with low average molecular weight, typically below about 1 million g / mol, the average molecular weight is measured using a Brookfield viscosity measurement at a temperature of 23° C. and a polymer concentration of 10%. The molecular weight [g / mol] is calculated from the formula 1 million * 0.77 * ln(viscosity [mPas]). In practice, this means that for polymers where the Brookfield viscosity can be measured and the calculated value is less than 1 million g / mol, the calculated value is the acceptable MW value. If the Brookfield viscosity cannot be measured or if the calculated value is greater than 1 million g / mol, the intrinsic viscosity is used to determine the MW value as described above.

[0069] In addition to the synthetic polymer component, the composition comprises a cationic polymer component, such as a cationic starch component of natural origin. In some embodiments, the cationic starch component is cationic unfloured starch. In this specification, this means a starch modified only by cationization, which is non-degraded and non-crosslinked. In some embodiments, the cationic starch component comprises starch units, at least 70% by weight, preferably at least 80% by weight, more preferably at least 85% by weight, even more preferably at least 90% by weight, even more preferably at least 95% by weight, of which have an average molecular weight MW of more than 20,000,000 g / mol, preferably 50,000,000 g / mol or more, more preferably 100,000,000 g / mol or more, even more preferably 200,000,000 g / mol or more. When the cationic starch component is not degraded, the length of the starch molecules provides a good three-dimensional network effect, leading to suitable interactions with not only the synthetic polymer component, but also with other components of the fiber raw material, such as fibers and / or inorganic fillers, as well as cationic strength agents added separately to the fiber raw material.

[0070] The cationic starch component may be starch from potato, waxy potato, rice, corn, waxy corn, wheat, barley, sweet potato or tapioca. Preferably, the cationic starch component is waxy corn starch and / or waxy potato starch. According to a preferred embodiment, the cationic starch component has an amylopectin content of 70% or more, preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, sometimes even more preferably 95% or more.

[0071] The cationic starch component is in the form of an aqueous solution, which means that the starch is dissolved in water, for example by cooking. Cooking may be carried out at a temperature of 60-135°C.

[0072] The starch can be cationized in any suitable manner. Preferably, the starch is cationized with 2,3-epoxypropyltrimethylammonium chloride or 3-chloro-2-hydroxypropyl-trimethylammonium chloride, with 2,3-epoxypropyltrimethylammonium chloride being preferred. It is also possible to cationize the starch with a cationic acrylamide derivative, such as (3-acrylamidopropyl)trimethylammonium chloride.

[0073] The cationic starch component may have a degree of substitution of 0.025 to 0.3, preferably 0.03 to 0.16, more preferably 0.045 to 0.1. The degree of substitution is relative to the degree of cationization of the starch. Cationic starches having a relatively high cationicity as defined are preferred for use in the composition.

[0074] In one preferred embodiment, the composition does not include a synthetic cationic polymer.

[0075] The composition is a mixture of a synthetic polymer component and a cationic polymer component, such as a cationic starch component. The components of the composition may be mixed well before the composition is added to the fiber raw material. That is, the composition is added to the raw material as a single solution. In this specification, the mixture of a synthetic polymer component and a cationic polymer component is understood as a blend or combination of an existing synthetic polymer component and a starch component. Both components are in the form of a solution or colloid when mixed. In other words, the mixture should not be interpreted as covering a composition obtained by polymerizing a monomer of a synthetic polymer in the presence of a cationic polymer component, thereby forming a starch graft.

[0076] In some embodiments, the composition can be prepared by mixing a cationic polymer component, such as a cationic starch component, with a solution of the synthetic polymer component, preferably at a pH of <3.5. If the pH upon mixing is higher than 4.5, there is a risk of gel formation, especially if the solids content of the composition is greater than 12% by weight.

[0077] The synthetic polymer component, when mixed with the starch component, may be in the form of an aqueous solution or suspension.

[0078] In some embodiments, a solution of a cationic polymer component, such as a cationic starch component, and a solution of a polymer component may be mixed prior to addition to the feedstock, provided that the solids concentration of each of the two solutions is less than 12% by weight, preferably less than 10% by weight. Preferably, the cationic polymer component and the synthetic polymer component are allowed to interact with each other prior to adding the composition to the fiber feedstock to ensure the formation of a polyionic complex.

[0079] In some embodiments, the compositions of the present invention may be prepared on-site. That is, the synthetic polymer component and the cationic polymer component may be dry or transported separately to the site of use. At the site of use, the synthetic polymer component and the cationic polymer component are optionally dissolved and / or diluted and mixed to prepare an aqueous composition. In this case, the risk of the composition deteriorating during transportation or storage is reduced. In particular, the cationic starch component is susceptible to microbiological degradation and would lose performance if decomposed.

[0080] When the composition is prepared or stored as a stock solution with a high solids content (e.g., greater than 10% by weight), the pH value is less than 3.5, preferably less than 3. It has been observed that a low pH improves mixing of the synthetic anionic and cationic polymeric components and provides a homogenous composition with the desired viscosity. In a preferred embodiment, the composition has a Brookfield viscosity of less than 10,000 mPas, preferably less than 8,000 mPas, more preferably less than 6,000 mPas at pH 3.0 and a solids content of 14% by weight. In some embodiments, the viscosity of the composition is in the range of 2,000-10,000 mPas, preferably 2,500-6,500 mPas at pH 3.0 and 14% by weight solids. Viscosity values ​​were measured at room temperature using a Brookfield DV-I+, small sample adapter, 20 spindle 31, maximum speed. The viscosity of the composition at a pH below 3.5 and high solids content is suitable for proper handling of the composition in industrial processes, for example allowing for dilution by pumping and mixing the composition.

[0081] Generally, the composition has an anionic net charge from a pH value of about 3.8 or more. Polyionic complexes resulting from the interaction of the cationic polymer component with the synthetic polymer component can be formed to a significant extent already at a pH of about 3.2. When a composition having a pH below 3.5 and a high solids content (e.g., more than 10% by weight) is diluted with water, the pH of the composition changes as the water is added. Alternatively, the pH of the composition may be adjusted by the addition of a base. Usually, the composition is diluted with water before being added to the fiber raw material, and the pH is adjusted by dilution or by the addition of a base. Thereby, a composition solution having a pH value of 3, preferably at least 3.5, more preferably 3.5 to 4.0 is obtained. When the pH of the composition exceeds pH 5, the net charge of the composition becomes anionic. At pH 7, the net charge of the composition is always anionic.

[0082] In some embodiments, an amphoteric polymer having both anionic and cationic groups is introduced into the fiber material, preferably in place of the composition, which provides a charge density of 0.05 to 1.5 meq / g when measured at pH 2.8, and -0.2 to -3 meq / g when measured at pH 7.0.

[0083] In some embodiments, an IPN (Interpenetrating Polymer Network) material is introduced into the fiber raw material, preferably in place of the composition, which provides a charge density of 0.05 to 1.5 meq / g when measured at pH 2.8, and -0.2 to -3 meq / g when measured at pH 7.0.

[0084] In some embodiments, a polymer having both anionic and cationic groups, preferably an amphoteric polymer and / or an interpenetrating polymer network material, is introduced into the fiber raw material, preferably instead of the composition, where the amphoteric polymer and / or the interpenetrating polymer network material provides the charge density described above.

[0085] In some embodiments, the composition is introduced in an amount of 5-50 kg / t, preferably 10-35 kg / t, more preferably 15-30 kg / t, based on the dry weight of the fibre raw material.

[0086] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide or mixtures thereof are introduced in an amount of 1 kg / t to 8 kg / t, preferably 2 kg / t to 6 kg / t, more preferably 2 kg / t to 4 kg / t, dry weight based on the dry weight of the fiber raw material.

[0087] In some embodiments, the starch comprises native starch, cooked starch, uncooked starch, cationic starch, native chemically modified starch, physically modified polymer-grafted starch, enzyme modified starch, anionic starch, amphoteric starch, crosslinked starch, pregelatinized starch, swelling starch, or granular starch, or mixtures thereof.

[0088] In some embodiments, the starch is introduced in an amount of from 1 kg / t to 100 kg / t dry weight, based on the dry weight of the fiber raw material.

[0089] In some embodiments, the cationic starch is introduced in an amount of from 4 kg / t to 20 kg / t dry weight, based on the dry weight of the fiber raw material.

[0090] In some embodiments, the non-ionic starch is introduced in an amount of from 1 kg / t to 100 kg / t dry weight, based on the dry weight of the fiber raw material.

[0091] In some embodiments, the pH of the fiber raw material is adjusted to a pH value of 5 to 9, preferably 7 to 8, prior to introducing the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof into the fiber raw material.

[0092] In some embodiments, the electrical conductivity of the textile material is adjusted to between 0.1 mS / cm and 3 mS / cm, preferably between 0.1 mS / cm and 1 mS / cm, prior to the introduction of the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof to the textile material. In some embodiments, the electrical conductivity is adjusted with a material consisting of 70% calcium acetate, 20% sodium sulfate and 10% sodium bicarbonate.

[0093] In some embodiments, a sizing chemical, fixing agent, wet strength agent, drainage aid, or mixtures thereof is introduced to the fibrous material after or before the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to the fibrous material.

[0094] In some embodiments, a sizing agent, fixing agent, wet strength agent, drainage aid, or mixtures thereof is introduced to the fibrous raw material prior to introducing the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fibrous raw material.

[0095] In some embodiments, the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to a fiber raw material prior to introducing a sizing agent, fixing agent, wet strength agent, drainage aid, or mixtures thereof to the fiber raw material.

[0096] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to the fibrous raw material prior to introducing the sizing agent to the fibrous raw material.

[0097] In some embodiments, the sizing agent, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are simultaneously but separately introduced to the fibrous raw material.

[0098] In some embodiments, the sizing agent, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, or mixtures thereof, are introduced to the fiber raw material as a mixture.

[0099] In some embodiments, the sizing agent comprises an alkyl ketene dimer (AKD), an alkenyl succinic anhydride (ASA), rosin, or a mixture thereof.

[0100] In some embodiments, the AKD, ASA, rosin or mixtures thereof, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced as a mixture to the fiber raw material, preferably before the composition is introduced to the fiber raw material.

[0101] In some embodiments, the AKD, ASA, rosin or mixtures thereof, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced as a mixture to the fiber raw material, preferably after the composition is introduced to the fiber raw material.

[0102] In some embodiments, the AKD, ASA, rosin, polyamidoamine epichlorohydrin, glyoxalate polyacrylamide, starch, or mixtures thereof are introduced to the fiber raw material as a mixture, preferably prior to introducing the composition to the fiber raw material.

[0103] In some embodiments, the AKD, ASA, rosin, polyamidoamine epichlorohydrin, glyoxalate polyacrylamide, starch, or mixtures thereof are introduced to the fiber raw material as a mixture, preferably after the composition is introduced to the fiber raw material.

[0104] In some embodiments, the AKD, ASA, rosin or mixtures thereof are incorporated in an amount of 0.1-4%, preferably 0.5-1.5%, based on the dry weight of the fiber material.

[0105] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide or mixtures thereof are introduced in an amount of 1-8 kg / t dry weight, preferably 2-4 kg / t dry weight, based on the dry weight of the fiber raw material.

[0106] In some embodiments, the fixing agent, the drainage aid, or a mixture thereof comprises aluminum sulfate (ALS), polyaluminum chloride (PAC), poly(diallyldimethylammonium chloride) (PDACMAC), cationic polyacrylamide (CPAM), or a mixture thereof.

[0107] In some embodiments, the wet strength agent comprises polyamide epichlorohydrin (PAE), glyoxalated polyacrylamide (GPAM), starch, or mixtures thereof. In some embodiments, the wet strength agent is added after the addition of a sizing agent, but before the composition is added to a fiber raw material.

[0108] In some embodiments, a fiber material is obtained that comprises cellulosic fibers, the fiber material having a consistency of 0.1%-10%, preferably 0.2%-1.0%, more preferably 0.2%-0.5%.

[0109] In some embodiments, the fiber raw materials comprising cellulosic fibers include natural fibers, synthetic fibers, or mixtures thereof. The fibers are preferably plant-based fibers, including recycled, chemical and / or mechanical hardwood and softwood pulp, sugarcane (such as bagasse), bamboo, barley, wheat, corn, oat, rice, rye, tomato, sorghum, rapeseed, palm oil plants, flax, hemp, ramie, cotton, kenaf, jute, banana, hemp, peat, sphagnum moss, or mixtures thereof.

[0110] In some embodiments, the cationic polymer component comprises a starch derivative such as hydroxypropylated starch, nanocellulose, microfibrillated cellulose, lignocellulose-based derivatives, chitosan, alpha glucan, polyhydroxyalkanoates, polylactic acid, cationic starch, or mixtures thereof, preferably cationic starch, chitosan, nanocellulose, microfibrillated cellulose, lignocellulose-based derivatives, or mixtures thereof.

[0111] According to a second aspect, the invention provides a molded fiber product comprising a composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and −0.2 to −3 meq / g when measured at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; Includes.

[0112] In some embodiments, the molded fiber comprises polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof.

[0113] In some embodiments, the molded fiber product comprises a pigment.

[0114] In some embodiments, the molded textile is a thermoformed textile, preferably a heat pressed, heat press dried, heat pressed textile or a thermoformed textile.

[0115] In some embodiments, the amount of fiber in the molded fiber product is 50wt.%-99wt.%, preferably 80wt.%-97wt.%, more preferably 90wt.%-97wt.%, based on the dry weight of the molded fiber product.

[0116] In some embodiments, the amount of the composition in the molded fiber product is from 0.5 wt.% to 10 wt.%, preferably from 1.5 wt.% to 3 wt.%, based on the dry weight of the molded fiber product.

[0117] In some embodiments, the amount of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof in the molded fiber product is from 0.05 wt.% to 0.8 wt.%, preferably from 0.2 wt.% to 0.4 wt.%, based on the dry weight of the molded fiber product.

[0118] In some embodiments, the amount of pigment in the molded textile product is from 0.01 wt.% to 5 wt.%, preferably from 0.5 wt.% to 4 wt.%, based on the dry weight of the molded textile product.

[0119] In some embodiments, the molded fiber product includes a sizing agent, a fixing agent, or a mixture thereof.

[0120] In some embodiments, the molded textile product comprises a sizing agent, fixing agent, drainage aid, or mixtures thereof. In some embodiments, the amount of sizing agent, fixing agent, drainage aid, or mixtures thereof in the molded textile product is between 0.1 wt.% and 5 wt.%, preferably between 0.5 wt.% and 2.5 wt.%, based on the dry weight of the molded textile product.

[0121] In some embodiments, the shaped fiber product comprises a food package, a food service article, a beverage package, a beverage service article, a merchandise package, or a merchandise service article, preferably a food service or packaging article such as an ovenable tray, a microwaveable tray, a clamshell box, other food boxes, soup cups, raw meat or poultry trays, plates, or cup lids.

[0122] In some embodiments, the shaped fiber product is produced by the process of the present invention.

[0123] According to a third aspect, the present invention provides the use of a composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; the synthetic polymer component and the cationic polymer component impart to the composition a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and -0.2 to -3 meq / g when measured at pH 7.0, In some embodiments, the composition comprises polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or a mixture thereof; Some embodiments include pigments to improve the grease and oil resistance of the molded fiber.

[0124] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are used in addition to the composition to improve the grease and oil resistance of the thermoformed textile products.

[0125] In some embodiments, in addition to the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof and the composition, a pigment is used to improve the grease and oil resistance of the thermoformed textile product.

[0126] In some embodiments, in addition to polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, the composition, and the pigment, sizing agents, wet strength agents, fixing agents, drainage aids, or mixtures thereof are used to improve the grease and oil resistance of the thermoformed textile products. [Example]

[0127] Example 1 according to the present invention

[0128] First, 0.1-0.3% (dry weight) of AKD is added to a fiber raw material having a consistency of 0.3-0.5%. The fiber raw material is made from 100% birch kraft pulp. Next, 0.3-0.5% (dry weight) of polyamide epichlorohydrin (PAAE) is added to the fiber raw material. Then, 1-3% (dry weight) of a composition (composition B) containing at least one synthetic anionic polymer with a molecular weight of 300-900 kDa and a cationic polymer is added to the fiber raw material. After each addition of the agent to the fiber raw material, it is mixed under turbulent conditions for at least 1 minute before the addition of the next agent and the formation of a vacuum.

[0129] Example 2, Comparative Example

[0130] The same methods and chemicals were used to prepare and characterize the two-dimensional molded products / sheets as in Example 1, except that instead of composition B, comparative composition A was used. Comparative composition A is a mixture of anionic and cationic polymers with molecular weights of 300-700 kDa.

[0131] Two-dimensional (2D) part / sheet preparation

[0132] After introducing the chemicals described in Example 1 and Example 2 into the fiber raw material, the fiber raw material is vacuum molded under a vacuum of 200-500 mBar against a forming wire with a flat circular shape of 10 cm diameter and an opening of 200-400 microns to a dryness of 20-30% using a Dynamic Drainage Analyzer (DDA). The wet 2D molded product / sheet with a dry weight of 200-800 g / m2 is then hot-press dried between metal plates at 130-200 °C until a dryness of 94-99% is reached, and thermoformed to a thickness of 0.2-0.8 mm. The hot-press dried and thermoformed 2D fiber molded product / sheet is shown in Figure 2.

[0133] The two-dimensional fiber molded product can be hot pressed and / or thermoformed to a density of 0.5 g / cm3 to 1.5 g / cm3, preferably 1.0 to 1.2 g / cm3, and a thickness of 0.1 to 1.2 mm, preferably 0.2 to 0.8 mm.

[0134] Three-dimensional (3D) part preparation

[0135] After the chemicals are introduced into the fiber raw material, a 3D forming wire with a suction mold is immersed into the fiber raw material, and the fiber raw material is pulled out of the 3D wire with an opening of 200-400 microns under a vacuum of up to 900 mBar to form the fiber raw material. The formed 3D part is pulled out of the fiber raw material and the liquid components are removed by vacuum suction assistance until the dryness of the wet-formed 3D product is 33% on average. The wet-formed 3D part is then transferred to a heated counter mold (130-200 °C), hot-press dried, and thermoformed to a thickness of 0.2-1.2 mm and a final dryness of 94-96%. The dried 3D fiber part is shown in Figure 3.

[0136] The 3D molded product can be hot-press dried and thermoformed to a wall thickness of 0.1 mm-1.2 mm (e.g., 0.5 mm-0.8 mm), length of 5 cm-50 cm, width of 5 cm-50 cm, and depth of 2 cm-20 cm.

[0137] Oil and grease resistance test

[0138] The oil and fat tests were performed using the test method based on the standard ASTM F119-82:2015. The grease tests were performed using the test method based on the standard TAPPIT559:2012.

[0139] As can be seen from FIG. 1, the wet-formed and (through-thickness) thermoformed molded parts (2D molded parts / sheets) according to the invention (composition B) show improved oil resistance compared to the zero test (only fiber raw materials including cellulosic fibers, no chemicals added) and the comparative composition A.

[0140] The above description provides a complete and informative description of the best mode for carrying out the invention currently contemplated by the inventors using non-limiting examples of specific implementations and embodiments. However, as will be apparent to those skilled in the art, the details of the above-described embodiments do not limit the invention and may be implemented in other embodiments using equivalent means or combinations of various embodiments without departing from the characteristics of the invention.

[0141] Moreover, features of the exemplary embodiments disclosed above may be employed without the corresponding use of other features.Accordingly, the foregoing description should be considered as merely illustrative of the principles of the present invention, and not in limitation thereof.The scope of the present invention is limited only by the appended claims.

Claims

1. 1. A method for improving the grease and oil resistance of a molded textile product, comprising: Obtaining a fiber raw material comprising cellulosic fibers; introducing a composition into said fiber raw material; wherein the composition comprises a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; and wherein the synthetic polymer component and the cationic polymer component provide the composition with a charge density of 0.05 to 1 meq / g when measured at pH 2.8 and -0.2 to -3 meq / g when measured at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, to the fiber raw material; forming the fiber raw material; A method comprising:

2. 10. The method of claim 1, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material.

3. 3. The method according to claim 1 or 2, wherein a pigment is introduced into the fibre raw material.

4. The method of any one of claims 1 to 3, wherein the fibrous material is formed into a sheet.

5. The method of claim 4 , wherein the sheet is formed into a three-dimensional article.

6. The method according to any one of claims 1 to 3, wherein the fibrous material is formed into a three-dimensional product.

7. 4. The method according to claim 1, wherein the fibrous material is wet shaped and the wet shaped fibrous material is formed into a three-dimensional product.

8. 8. The method of any of claims 1 to 7, wherein the forming comprises wet forming, wet molding, vacuum forming, vacuum forming, extrusion forming, extrusion molding, thermoforming, dry forming, heat pressing, heat press drying, hot molding, heat press forming, thermoforming, or a combination thereof.

9. 9. The method according to claim 1, wherein the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof and the composition are introduced sequentially into the fiber raw material.

10. 9. The method according to any one of claims 1 to 8, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material before introducing the composition into the fiber raw material.

11. 9. The method according to any one of claims 1 to 8, wherein the composition is introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof being introduced into the fiber raw material.

12. The method of any of claims 1 to 8, wherein the synthetic polymer component and the cationic polymer component are introduced sequentially into the fiber raw material.

13. 9. The method of claim 1, wherein the cationic polymer component is introduced into the fiber raw material prior to introducing the synthetic polymer component.

14. 9. The method of claim 1, wherein the synthetic polymer component is introduced into the fiber raw material prior to the introduction of the cationic polymer component.

15. 11. The method of any of claims 1 to 10, wherein the synthetic polymer component, the cationic polymer, and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are sequentially introduced into the fiber raw material.

16. 11. The method according to any of claims 1 to 10, wherein the synthetic polymer component and the cationic polymer component are sequentially introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof being introduced into the fiber raw material.

17. 11. The method according to any of claims 1 to 10, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof is introduced to the fiber raw material, followed by sequentially introducing the synthetic polymer component and the cationic polymer to the fiber raw material.

18. 11. The method of any of claims 1 to 10, wherein the synthetic polymer component is introduced to the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof, and then the cationic polymer component is introduced to the fiber raw material.

19. 11. The method of any of claims 1 to 10, wherein the cationic polymer component is introduced to the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof, and then the synthetic polymer component is introduced to the fiber raw material.

20. 20. The method according to any of the preceding claims, wherein the composition is introduced in an amount of 5 to 50 kg / t, preferably 15 to 35 kg / t, more preferably 20 to 30 kg / t, based on the dry weight of the fibre raw material.

21. 21. The method according to any of the preceding claims, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced in an amount of 1 to 8 kg / t, preferably 2 to 6 kg / t, more preferably 2 to 4 kg / t, based on the dry weight of the fibre raw material.

22. 22. The method according to any of the preceding claims, wherein the pH of the fibre raw material is adjusted to a pH value between 5 and 9, preferably between 7 and 8, before the composition and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fibre raw material.

23. 23. The method according to any of the preceding claims, wherein the electrical conductivity of the fibre material is adjusted to between 0.05 mS / cm and 6 mS / cm, preferably between 0.1 mS / cm and 1 mS / cm, before the composition and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fibre material.

24. 24. The method according to any of the preceding claims, wherein a sizing agent, fixing agent, or mixtures thereof is preferably introduced into the fibre raw material before the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced into the fibre raw material.

25. 25. The method of any of claims 1 to 24, wherein an amphoteric polymer and / or an interpenetrating polymer network material having both anionic and cationic groups is introduced into the fiber raw material, preferably instead of the composition, wherein the amphoteric polymer and / or the interpenetrating polymer network material provides the charge density.

26. A molded fiber product comprising a composition, the composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; and the synthetic polymer component and the cationic polymer component provide the composition with a charge density of from 0.05 to 1 meq / g when measured at pH 2.8 and from −0.2 to −3 meq / g when measured at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; Including, 26. A composition produced by the method of any one of claims 1 to 25.

27. 27. The molded fiber product of claim 26, comprising a food package, a food service item, a beverage package, a merchandise package, preferably an ovenable tray, a microwaveable tray, a clamshell box, other food box, a soup cup, a raw meat and poultry tray, a plate or a cup lid.

28. Use of a composition, said composition comprising: a synthetic polymer component which is a copolymer of acrylamide and at least one anionic monomer and has an anionic character of 1-60 mol %; a cationic polymer component; and the synthetic polymer component and the cationic polymer component provide the composition with a charge density of from 0.05 to 1 meq / g when measured at pH 2.8 and from −0.2 to −3 meq / g when measured at pH 7.0; and In some embodiments, the composition comprises polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or a mixture thereof; In some embodiments, the molded fiber includes a pigment to improve the grease and oil resistance of the molded fiber. composition.